OPTIMALISASI BOOKS IN PRINT (BIP) SEBAGAI SARANA PROMOSI DAN ALAT SELEKSI PENGEMBANGAN KOLEKSI - Irham Hanif Nabawi (Maktabatuna, 2020)
This article aims to provide input on the efforts needed by the ISBN Team to optimize the use of Books in Print (BIP). The recommendation offered is the placement of Books in Print (BIP) on ISBN web pages so that BIP can be quickly, interactively and more widely utilized, both by the publisher as a promotional tool and by the library as a selection tool in collection development.